Memetakan Pola Kunjungan Wisatawan Mancanegara ke Nusa Tenggara Barat untuk Pengembangan Bisnis Kepariwisataan - Ira Indayani; Lisna Ayu; Amara Aulia; Karina Utami; Herie Saksono (ALETHEIA: Jurnal Sosial & Humaniora, Inovasi, Ekonomi, dan Edukasi, 2024)
West Nusa Tenggara (NTB) has natural beauty, superior human resources, and abundant cultural riches, making it a tourist attraction. The progress of the tourism industry has stimulated the growth of various types of businesses and various business sectors in different economic sectors. Visits from foreign tourists are the starting point for starting a business. This potential must be identified and mapped to be able to open new business spaces and provide excellent, ultimate, optimal, and sustainable quality tourism services. Through this study, tourism stakeholders can formulate tourism business development strategies. This study seeks to map the visiting patterns of foreign tourists visiting NTB. The approach used is quantitative with a focus on measuring the rate of foreign tourist visits per month from 2015-2022. The Central Statistics Agency and the NTB Provincial Tourism Office obtained secondary data on foreign tourist visits. The results of the analysis prove that there are fluctuations in foreign tourist visits to NTB. Since 2015-2019, it has shown a quite significant trend of increasing visits. However, in 2020-2022 there was a drastic decline due to the Covid-19 pandemic. It was also found that there was a seasonal visiting pattern in the peak months, namely: July, August, November and December. Ideally, this pattern should be scrutinized so that strategies can be immediately developed to promote the unique tourism resources that have made NTB a major attraction for foreign tourists. In the end, the essence of data on foreign tourist visits has inspired the Government, Regional Government, and tourism stakeholders to innovate, prepare marketing strategies, promote them digitally, and diversify tourism products. During the quiet months, visitors can be used to improve infrastructure, public facilities, and services in tourism destinations that prioritize environmental sustainability, and economic, social, and cultural resilience.